Unusual salting effects in ionic liquid solutions - Nanda, Raju; Kumar, Anil (Indian Journal of Chemistry Section A-Inorganic Bio-Inorganic Physical Theoretical & Analytical Chemistry, 2013)
Unusual salting effects of salting-out agents like LiCl and NaCl and salting-in agents like LiClO4 and NaClO4 in ionic liquid solutions are reported. It is observed that the salting behavior in water can be altered in the presence of ionic liquids. It is demonstrated that the salting-in agents in the presence of the ionic liquids with higher alkyl chain can display unusual fall and rise in the viscosity of the systems. On the other hand, no change in the behavior of the salting-out agents is noted in these ionic liquids. A tentative explanation is proposed for the observed viscosity data in these systems.
Keywords: Cationic ring; ionic liquids; Salting effects; viscosity